Managerialism for Economic Development - Prasad, P. author. aut Link
170 p.
Keywords: That a developing economy needs management even more than resources is now becoming abundantly clear to all students of growth. There was perhaps a facile assumption in the earlier years that the rate of growth in a developing country depended in almost direct proportion to two factors: the resources available within the country, the land, water, minerals, savings and other relevant inputs; and the initial importation of aid from without, in terms of capital and skills not available within - but the factor of good management was somehow ignored, as also the attitudes of the people and their leadership to growth. These two factors are now coming into their own as being crucial to development and there is a new appreciation of the need for a good supply of well trained managers and providing them with an environment that is permissive and encouraging. These essays are a timely analysis of this new-felt need, and a valuable source of new leads and hypotheses, for they examine the multi-facets of the problem of India's growth, but with keeping the professional manager squarely in the middle of the study. And after all it is he upon whom the major responsibility for develop ment and growth will depend, given the chance. The contributors to this symposium are seven young Indians, all management educators of distinction at universities in the United States, and one hopes that they will themselves pick up some of the leads and pursue them. P. L.